(untitled) (The Pakistan Development Review, 1994)
The supply response functions for beef, mutton, poultry meat, eggs, and fresh milk are estimated using the polynomial price lag model, and that of fish meat production using the stock adjustment model. Both the production and domestic consumption of these foods are then projected over the period 1993-94 through 2004-05 using the estimated supply response functions and the existing estimates of demand parameters assuming trend growth of exogenous variables. In the case of mutton and fresh milk there is excess demand, while in the rest of the cases surplus production is predicted. A significant proportion of the anticipated excess demand for mutton and fresh milk can be eliminated by increasing the rate of credit supply to these sub-sectors.